STUDI KEBUGARAN JASMANI SISWA KELAS V SEKOLAH DASAR NEGERI 26 AIR TAWAR TIMUR KOTA PADANG - Adila, Nur; Deswandi; Astuti, Yuni; Oktavani, Lucy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the importance of physical education, sports, and health (PJOK) in shaping a healthy and fit generation. However, at State Elementary School 26 Air Tawar Timur, particularly among fifth-grade students, physical fitness tests and measurements had never been conducted, leaving students' physical conditions unknown. The aim of this study was to determine the physical fitness level of male and female fifth-grade students at the school. A quantitative descriptive method was employed, utilizing tests and measurements with the Indonesian Student Fitness Test (TKSI) Phase C instrument, which includes hand-eye coordination (Child Ball), accuracy (Tok Tok Ball), agility (Shuttle Run), abdominal muscle strength (Move The Ball), and cardiorespiratory endurance (600-meter Run). The sample consisted of 27 students (16 males and 11 females) selected through purposive sampling, and the collected data were analyzed using frequency distribution. The results revealed that the physical fitness level of male students fell into the poor category with an average score of 12, while female students also fell into the poor category with an average score of 11. Overall, no students achieved the good or excellent categories. In conclusion, the physical fitness level of fifth-grade students at SDN 26 Air Tawar Timur, Padang City, is classified as low. Therefore, improvement efforts are necessary through learning modifications, limiting gadget use, and enhancing sports facilities and infrastructure to optimally support students' physical activities.